Performances of pretreated ceria-zirconia nanomaterials/H2O2 system for the degradation of Orange II dye. (2016) - Hamoud, Houeida Issa; Azambre, Bruno; Finqueneisel, GisÁ¨le
In this work, the parameters affecting the reactivity of non-sulfated and sulfated commercial ceria-zirconia (Cex Zr1−x O2 ) nanomaterials with varying Ce content (x = 1, 0.80, 0.50, 0.21, 0) towards the degradation of Orange II dye have been evaluated. Characterisation of the catalysts was performed using nitrogen adsorption, XRD, Raman, TGA thermogravimetry and DR-UV-Vis spectroscopy. Briefly, it can be deduced that the sulfation treatment mostly affects the Ce rich catalysts by increasing the crystallite size and lowering the specific surface area. It is shown that the H2 O2 dissociates on Ce (III) surface sites to yield peroxide-like species. Such species played a key role in enhancing the discoloration of the dye under dark and UV-Vis conditions. By contrast, the sulfation treatment is unfavorable for the adsorption of H2 O2 . Sulfates interfere in the formation and the chemical stability of the surface peroxide species via pre-chelating the cerium surface centers, resulting in reducing the catalytic activity of catalysts, especially for CeO2 .